Hubungan Komunikasi dan Sikap dengan Implementasi Kebijakan Pajak Reklame di Kawasan Simpang Lima Semarang - Supriyanto, Supriyanto; Purnaweni, Hartuti; Widowati, Nina (Journal of Public Policy and Management Review, 2014)
Advertisement tax is one of the Regencial / Municipal tax. to help in increasing enabel the goverment tax manage earning to execute development and enable the goverment tax manage its own area. However, in reality implementation of this policy implementation has not brought yet resulted well enaugh.The results of this research proved that There is a significant relationship between attitude and communication forward policy implementation as evidenced from the results Concordance Kendall Coefficient (W) which shows the rate of 0,893 W and ð‘‹2 test of significance produce ð‘‹2 value of 85.72. This then consulted with ð‘‹2 tables with significance level of 5% = 55.75 indicates that the observation ð‘‹2 = 85.72 > ð‘‹2 = 55.75% Table 5 so that it can be concluded that the hypothesis can be accepted.